The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1049/iet-nbt.2018.5122
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles and silver salt (AgNO3) elicits morphogenic and biochemical variations in callus cultures of sugarcane

Abstract: The research work was arranged to check the role of AgNPs and silver ions on callus cells of sugarcane (Saccharum spp. cv CP-77,400). AgNPs were synthesized chemically and characterized by UV-Vis spectra, XRD and SEM. AgNPs and silver ions were applied in various concentrations (0, 20, 40, 60 ppm) to sugarcane calli and the induced stress was characterized by studying various morphological and biochemical parameters. AgNPs and silver ions treatments produced high levels of malondialdehyde, proline, proteins, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Similarly, AgNPs at 40 and 60 mg/L caused an enhancement in biomass accumulation in callus cultures of sugarcane ( Saccharum spp.) (Iqbal et al 2019 ). Contrarily, it has been observed that fresh and dry mass of pearl millet ( Pennisetum glaucum L.) seedlings reduced significantly after 24 h exposure to increasing concentration of AgNPs (Khan et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, AgNPs at 40 and 60 mg/L caused an enhancement in biomass accumulation in callus cultures of sugarcane ( Saccharum spp.) (Iqbal et al 2019 ). Contrarily, it has been observed that fresh and dry mass of pearl millet ( Pennisetum glaucum L.) seedlings reduced significantly after 24 h exposure to increasing concentration of AgNPs (Khan et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Silver sulfadiazine is notably the gold standard for the treatment of local burns [86]. With the development of nanotechnology, many studies have shown that silver nanoparticles exhibit prolonged and controlled release of silver ions; this can improve biological safety and reduce the frequency of clinical dressing replacements required with the use of silver salts [87]. Silver nanoparticles have strong bactericidal properties that have been observed in both in vivo and in vitro experiments [88][89][90][91].…”
Section: Cs-metal Nanocompositesmentioning
confidence: 99%